Evidence for Emergence of Sex-Determining Gene(s) in a Centromeric Region in Vasconcellea parviflora. Issue 2 (5th December 2014) - Iovene, Marina; Yu, Qingyi; Ming, Ray; Jiang, Jiming
Abstract: Sex chromosomes have been studied in many plant and animal species. However, few species are suitable as models to study the evolutionary histories of sex chromosomes. We previously demonstrated that papaya ( Carica papaya ) (2 n = 2 x = 18), a fruit tree in the family Caricaceae, contains recently emerged but cytologically heteromorphic X/Y chromosomes. We have been intrigued by the possible presence and evolution of sex chromosomes in other dioecious Caricaceae species. We selected a set of 22 bacterial artificial chromosome (BAC) clones that are distributed along the papaya X/Y chromosomes. These BACs were mapped to the meiotic pachytene chromosomes of Vasconcellea parviflora (2 n = 2 x = 18), a species that diverged from papaya ∼27 million years ago. We demonstrate that V. parviflora contains a pair of heteromorphic X/Y chromosomes that are homologous to the papaya X/Y chromosomes. The comparative mapping results revealed that the male-specific regions of the Y chromosomes (MSYs) probably initiated near the centromere of the Y chromosomes in both species. The two MSYs, however, shared only a small chromosomal domain near the centromere in otherwise rearranged chromosomes. The V. parviflora MSY expanded toward the short arm of the chromosome, whereas the papaya MSY expanded in the opposite direction. Most BACs mapped to papaya MSY were not located in V. parviflora MSY, revealing different DNA compositions in the two MSYs. These results suggest that mutation of gene(s) in the centromeric region may have triggered sex chromosome evolution in these plant species.